Transnational Law and Criminal Justice System: Highlighting Legislative and Procedural Challenges to combat Cyber Crime in the wake of CPEC - Saifullah, Rana; Roshan Shah, Sayeda Sassi (JISR management and social sciences & economics, 2023)
World Justice Project’s (WJP) Rule of Law Index 2022 ranked Pakistan globally at 129th out of 140 countries while on regional level Pakistan is ranked 5th out of 6 countries. Where Pakistan’s justice system is hitting the bottom in rule-of-law index, at the same time, the entire nation is celebrating China-Pakistan Economic Corridor (CPEC), which is a flagship project of Belt and Road Initiative (BRI) also known as OBOR. This is a Chinese master stroke in the cross-continental geo-economics of the world. With a heavy influx of Chinese businesses and Chinese nationals arriving in the country, the markets and Pakistani citizens are vulnerable to criminal activities including more sophisticated types of crimes such as crimes involving ICT. In particular, incidents of ATM skimming are rising in Karachi among other crimes. Foreign nationals are arrested include Chinese nationals; however, legislative and procedural lacunas and prosecution related defects eventually cause the prosecution version to collapse during trial. Therefore, this research study proposes strong legislative and judicial framework, human resource development including need for prompt initiatives in the subordinate judiciary. This research also highlights the need for having proper compliance of environmental and labor laws regulations. The research is based on mixed methodology. Quantitative analysis is conducted on the data collected through questionnaires from the sample of 50 respondents that include advocates, FIA investigation officers and public prosecutors. In addition, qualitative analysis is done through interviews of senior officers from NR3C as well as I.Os, students, academics and research economists from academia.